Determining the Effectiveness of Positive Psychology on Resilience and Depression Among Master’s Students at Payame Noor University of Karaj - Nokhbe Zare, Fatemeh; Mirzaei, Parvin; Mousavi Asl, Seyed Ali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The aim of this research was to determine the effectiveness of positive psychology on resilience and depression among master’s students at Payame Noor University of Karaj. Methods and Materials: This study employed an experimental methodology with a quasi-experimental design, specifically a pretest-posttest with a control group. The statistical population comprised all master’s students at Payame Noor University of Karaj. The sample size was considered to be 30 individuals. Data collection methods included both library and field approaches. The data collection instruments used in this study were two standardized questionnaires: the Connor-Davidson Resilience Scale and the Beck Depression Inventory (1978), along with a protocol for group-based positive psychological training and guidance. The data were analyzed using the Statistical Package for the Social Sciences, version 21 (SPSS). Descriptive statistics, including mean and standard deviation, were used in the pretest and posttest stages. To assess the normality of the variables, the Kolmogorov-Smirnov test was employed, and to examine homogeneity of variances, Levene’s test was used. Analysis of covariance (ANCOVA) was applied to compare the mean scores of the experimental and control groups and to account for the effect of pretest scores and other confounding variables on the posttest. Findings: The results indicated that positive psychology training had a significant impact on the resilience of the master’s students at Payame Noor University of Karaj. Conclusion: In sum, positive psychology training improved the resilience and depression levels of the students, with a more pronounced effect on resilience compared to depression.